2013
DOI: 10.1002/adsc.201300386
|View full text |Cite
|
Sign up to set email alerts
|

One Substrate – Seven Products with Different Prenylation Positions in One‐Step Reactions: Prenyltransferases Make it Possible

Abstract: Prenylated indole alkaloids derived from L‐tryptophan are widely distributed in nature and show diverse biological and pharmacological activities, usually distinct from their non‐prenylated precursors. Prenyltransferases catalyze the transfer reactions of prenyl moieties onto the indole nucleus and contribute largely to the structural diversity of these compounds. In this study, we demonstrate the acceptance of cyclo‐L‐homotryptophan‐D‐valine, an unnatural cyclic dipeptide, by eight prenyltransferases of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Compounds 42a−44a were synthesized as described in the literature (Dawidowski and Turlo 2014;Zeng et al 2005). Preparation of prenylated CDPs using prenyltransferases has been reported before (Fan and Li 2013;Wunsch et al 2015;Yin et al 2013;Yin et al 2007). All other cyclodipeptides used in this study were obtained from Bachem (Bubendorf, Switzerland) or synthesized as reported previously (Wollinsky et al 2012;Yu et al 2013).…”
Section: Chemicalsmentioning
confidence: 99%
“…Compounds 42a−44a were synthesized as described in the literature (Dawidowski and Turlo 2014;Zeng et al 2005). Preparation of prenylated CDPs using prenyltransferases has been reported before (Fan and Li 2013;Wunsch et al 2015;Yin et al 2013;Yin et al 2007). All other cyclodipeptides used in this study were obtained from Bachem (Bubendorf, Switzerland) or synthesized as reported previously (Wollinsky et al 2012;Yu et al 2013).…”
Section: Chemicalsmentioning
confidence: 99%
“…These soluble enzymes use predominantly tryptophan and other indole derivatives as prenyl acceptors but also accept a broad spectrum of aromatic compounds as substrates . Diprenylation of indole derivatives by one DMATS enzyme was observed in several cases. However, a gem -diprenylation has not been reported for such enzymes or for other soluble prenyltransferases. The sole example of gem -diprenylation of an aromatic substrate was described for the metabolon of HIPT1L and HIPT2 mentioned above …”
mentioning
confidence: 99%
“… 1 The demand for such diversely substituted indolic structures has led to the development of ever more efficient and direct methods for their synthesis, none more so than in the nascent field of C–H functionalization. 2 6 Within this realm, some inventive and practical chemistry has been developed to functionalize different positions around the indole ring, mainly through the innate reactivity of the C2, 3 C3, 4 and C5 5 sites and to a lesser extent C4 and C6. 6 The growing number of structurally and biologically fascinating natural and unnatural products bearing an indole substituent at C7 (i.e., 1 – 6 , Figure 1 ) has generated further interest in methods that expedite functionalization at this position.…”
mentioning
confidence: 99%